2004
DOI: 10.1097/01.alc.0000134231.48395.42
|View full text |Cite
|
Sign up to set email alerts
|

ADH1B*1, ADH1C*2, DRD2 (−141C Ins), and 5‐HTTLPR Are Associated With Alcoholism in Mexican American Men Living in Los Angeles

Abstract: Together, the data reveal unique genetic patterns in Mexican Americans that may be in part responsible for the heightened risk for alcoholism and alcohol-associated health problems in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 59 publications
6
61
1
Order By: Relevance
“…There was, however, a substantial difference between East Asians and Caucasians, because a significant association between allele *2 and the risk of alcoholism was detected for the former (RE OR ϭ 1.91 [95% CI 1.45, 2.53]) but not the latter. In sensitivity analysis, 5,26,29,31,45 the pattern of results was also similar. In a subgroup analysis for the men 6,32,39 (no study provided data for women), there was no association.…”
Section: Adh2mentioning
confidence: 62%
See 2 more Smart Citations
“…There was, however, a substantial difference between East Asians and Caucasians, because a significant association between allele *2 and the risk of alcoholism was detected for the former (RE OR ϭ 1.91 [95% CI 1.45, 2.53]) but not the latter. In sensitivity analysis, 5,26,29,31,45 the pattern of results was also similar. In a subgroup analysis for the men 6,32,39 (no study provided data for women), there was no association.…”
Section: Adh2mentioning
confidence: 62%
“…Data from 50 studies that investigated the association between any of the ADH2, ADH3, CYP2E1, and ALDH2 polymorphisms and alcoholism, and alcohol-induced liver disease, met the inclusion criteria and were included in the meta-analysis. Thirty-three studies dealt with ADH2, 2 [2][3]6,8,11,[26][27][29][30][31][32]37,[39][40][41][42][43][44]46,47,51 and 20 studies in CYP2E1. 6,11,26,31,32,35,[41][42][43]54,[57][58][59][60][61][62][63][64][65]67 To investigate the association between any of the four loci considered and alcohol-induced liver disease, ten studies dealt with ADH2, 5,6,[31][32][33]35,…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The hazard ratio of hospitalization for alcoholism in men and women with the slow alcohol degradation ADH1B Á 1/1 genotype was 3.9 (95% CI: 1.0-16) and 2.7 (95% CI: 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…There is strong evidence for a negative association between the ADH1B*2 allele (i.e., A allele at rs1229984) and alcohol dependence and alcohol consumption (Ehlers et al, 2012;Konishi et al, 2004;Li et al, 2011;Macgregor et al, 2009), as well as evidence for the ADH1B*3 allele (i.e., T allele at rs2066702) (Edenberg et al, 2006;Ehlers et al, 2007). Bierut et al (2012) reported reduced risk for alcohol dependence for the A allele at rs1229984 versus the G/G genotype in a combined sample of European Americans and African Americans.…”
mentioning
confidence: 99%